Perancangan Lanskap Sekolah Menuju Peningkatan Penerapan Program Adiwiyata SMKN 63 - Silia Yuslim; Etty Indrawati; Ida Bagus Rabindra; Olivia Seanders (Institut Pertanian Bogor, 2021)
The Study Program of Landscaping and Gardening (Program Studi Lanskap dan Pertamanan (LDP)), one of the study programs at SMKN 63 Jagakarsa, South Jakarta, needs guidance related to learning materials of landscape design. The purpose of providing landscape design materials for school members (teachers and students) is to increase the knowledge and skills of making landscape designs and optimize the function and beauty of the school's out space. It supports the behavior of the environmental awareness that the Adiwiyata program promotes. Community service activities in the form of socialization and training so that school members can design the landscape independently and distribute questionnaires to measure the level of achievement of the socialization and training were carried out. The case area to be designed is a corner garden in the front yard of SMKN 63. The activity results show that the participants' perceptions fall into the category of agreeing to strongly agree on the value of the benefits of the service material. Participants were very enthusiastic and active. Creativity and design making still need guidance. Evaluation in the following month shows the follow-up of the resulting design. This enthusiasm led to a cooperation agreement between SMKN 63 and a community service team from the Landscape Architecture Department, Faculty of Laskap Architecture and Environmental Technology, Trisakti University to foster school residents sustainably.